Evaluation testicular fine needle aspiration cytology and serum testosterone levels in dogs - Souza, Fabiana Ferreira de; Leme, Denise Pereira; Uechi, Edilson; Trinca, Luzia Aparecida; Lopes, Maria Denise (Brazilian Journal of Veterinary Research and Animal Science, 2004)
In order to verify alternative clinical approach in the reproductive evaluation of 4 adult dogs, the fine needle aspiration cytology (FNAC) and serum testosterone levels were used together with testicular volume measurement and semen analysis. FNAC was performed in both testes and serum testosterone concentrations were assayed in regular intervals during a 24h period. Results of semen analysis and FNAC were normal in dogs 1 and 3. In dog 2, small testes, poor semen quality, a high percentage of Sertoli cells and early spermatids were found suggesting testicular degeneration. In dog 4, a small right testicle, poor semen quality with low sperm concentration and an uncounted amount of spermatozoa in the FNAC indicated testicular degeneration due to an obstructive lesion; whereas high percentage of distal droplets, thicker left epididymis and normal FNAC of the left testis suggested a slow sperm transit. Testosterone circadian rhythm was clear in 3 of 4 dogs, although concentrations were low. Testicular volume, semen analysis and testicular FNAC could provide valuable information about spermatogenesis. In contrast, serum testosterone concentration was not clearly correlated with any reproductive characteristic of those dogs.